Multi-criteria exergoeconomic optimization for a combined gas turbine-supercritical CO2 plant with compressor intake cooling fueled by biogas from anaerobic digestion. (15th May 2021) - Al-Rashed, Abdullah A.A.A.; Afrand, Masoud
Abstract: An innovative combined gas turbine-supercritical CO2 cycle is suggested for efficient power production using biogas generated from biomass anaerobic digestion. To enhance the proposed system performance, its waste heat is recovered via absorption refrigeration for CO2 cooling at the compressor inlet of the S–CO2 cycle. Comprehensive exergoeconomic analysis is provided to assess its performance and to compare with the system without intake cooling. Also, multi-criteria optimization is conducted to maximize exergetic efficiency and to minimize the power cost. It is found that, the compressor inlet cooling brings about a considerable performance enhancement both thermodynamically and economically. Under the optimal operation it is shown that, the proposed system yields exergy efficiency of 56.69%, while efficiency of system without intake cooling is 45.24%, indicating enhancement by 25.3% via applying compressor intake cooling on S–CO2 cycle. The other interesting outcome is the fact that despite the higher investment costs for the system with inlet cooling (imposed by adding absorption refrigeration) it has lower values of unit product cost compared to the system without inlet cooling. Highlights: Biogas fueled combined gas turbine-supercritical CO2 cycle is proposed and analyzed. Absorption refrigeration powered by exhaust gas is used for CO2 compressor inlet cooling. Multi-criteria exergoeconomic optimization is applied to obtain the best operating point. Despite higher investment cost, lower product cost is found for the system with inlet cooling.